Analysis of Community-Based Waste Management through Waste Bank in Tinjomoyo Urban Village, Semarang City, Central Java - Sarful Anam; Arum Siwiendrayanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Waste is a problem that, until now, has been difficult for the Indonesian government to solve. The emergence of waste banks can make people aware of the need to manage waste properly. The community eventually became more educated about managing and sorting household waste. The household waste consists of used cardboard, used plastic drink bottles, used shoes, and other used items. If waste banks exist in a community and whether they have an impact on that community or other "aspects" is a question unto itself. This study aims to see the impact of waste banks on the community and help local governments realize effective waste bank management. The type of research used in this study is observational-descriptive research. In addition, interviews were also conducted with waste bank administrators, and questionnaires were distributed to waste bank customers. The data was analysed with simple quantitative descriptive. The results of this study reveal the underlying aspects of the establishment of a waste bank in Tinjomoyo Urban Village and the impact of the waste bank on the surrounding community, especially on waste bank customers. As a result, some people feel a positive impact from the waste bank in Tinjomoyo Urban Village.